Vagal control of myocardial contractility in humans. - Casadei, B (2001)
Until about 40 years ago, it was thought that the parasympathetic innervation of the mammalian heart was confined to supraventricular structures. Hence, neither the vagus nor its primary neurotransmitter, acetylcholine (ACh), were believed to have significant effects on the inotropic state of the ventricles or on their excitability. However, it is now well-established that vagal/muscarinic stimulation prolongs ventricular refractoriness in humans and has a small but distinct negative inotropic effect on the left ventricle, which is accentuated in the presence of elevated sympathetic activity (Löffelholz and Pappano, 1985). This brief review will consider the evidence for a vagal/ muscarinic regulation of left ventricular (LV) function in humans and discuss the mechanisms that may be responsible for this effect.